INDIA'S ROLE IN THE CHANGING CURRENTS OF WORLD POLITICS - Bane, Rekha Ramnath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India's rapidly growing economy, strategic importance of geographical location and democratic governance have made India an important nation-building country in world politics. India's growing role on the world stage, its strategic partnerships, economic influence and political initiatives are seen as important. India's role in world politics has evolved significantly. From the post-colonial period and the non-alignment movement to becoming an influential global power, India has come a long way. Due to its growing economic power, strategic geographical location and active participation in world politics, India is playing a significant role in shaping world politics. This article provides an in-depth analysis of changes in India's foreign policy, economic influence, defense policies and diplomatic relations.